Experimental measurements of propulsive factors in following and head waves. (June 2021) - Saettone, Simone; Taskar, Bhushan; Steen, Sverre; Andersen, Poul
Abstract: The results from resistance measurements in calm water and load-varying self-propulsion tests in calm water and regular head and following waves are presented. The experimental campaign is conducted in the large towing tank at SINTEF Ocean (formerly MARINTEK). The openly accessible hull of the single screw Duisburg Test Case is selected as the test case. The wave added resistance, ship motions RAOs, axial wake fraction, thrust deduction fraction, relative rotative efficiency, hull efficiency, propeller open-water efficiency, propeller efficiency behind ship, and propulsive efficiency are determined. Regarding the calculation of the thrust deduction fraction, the results of the experiments show the effect of utilizing the bare hull resistance instead of the linearly extrapolated ship resistance at zero propeller thrust. If the former is applied, the thrust deduction fraction will be dependent on the load of the propeller. If the latter is utilized, the thrust deduction fraction will be independent of the propeller loading. As expected, the wave added resistance is lower in following waves than in head waves. The heave and pitch motions are larger in head waves, whereas the surge motion is higher in following waves. The effective wake fraction is affected by both the propeller loading and the ship motions. In the case of the former, the higher the propeller loading, the lower the effective wake fraction. For the latter, a general decrease in effective wake fraction is noticed in head waves compared to calm water. On the contrary, the effective wake fraction is higher in following waves in comparison to calm water. The thrust deduction fraction computed with the extrapolated ship resistance appears to be slightly affected by the ship motions. However, a final conclusion was not drawn because of the large uncertainties in the measurements of this propulsive coefficient. The variation in propeller open-water efficiency is mainly related to the change in propeller loading. The relative rotative efficiency is barely affected by both the propeller loading and the motions of the ship. Except in the case of very large wave amplitudes, the hull efficiency is hardly influenced by the ship motions. The propulsive efficiency is primarily affected by the change in propeller open-water efficiency. Based on the results of the experimental campaign, overload tests in calm water provide a good estimation of the propulsion efficiency in waves for the selected case vessel.